The Mainland Chinese market for nature tourism in Hong Kong. Issue 5 (20th October 2017) - Chan, Chung-Shing; Chiu, Hoi Yan; Marafa, Lawal M.
ABSTRACT: Nature tourism has been emerged as an ecologically sensitive form of tourism in developed and developing countries. A large influx of tourists would have both benefits and adverse impacts on these destinations. With an increasing influence of Chinese market in many destinations and tourism activities worldwide, it is important to understand the perceptions and preferences of Chinese tourists toward natural attributes so that proper approaches to destination planning and marketing can be derived to better attract these segments of tourists and sustainably manage tourism resources. The results of an empirical study of a sample of Mainland citizens ( n = 430) to Hong Kong's nature areas show that (1) they exert a high degree of interest in participating in nature tourism; (2) female and older people are more interested in visiting natural environment; (3) these potential nature tourists from China prefer going to places in association with sea views, and engaging in photo-taking, non-commercial activities and less artificial elements; and (4) the nature tourism attributes form two factors related to aspects of educational needs and relaxation (an experiential factor), and nature-oriented but also convenient (a functional factor). These considerations can lead to the development of ecotourism products that are better suited to meeting the interests of mainland Chinese tourists, while also enriching the host experience.